Analysis of catRABC operon for catechol degradation from phenol-degrading Rhodococcus erythropolis - Veselý, M; Knoppová, M; Nesvera, J; Pátek, M (Applied microbiology and biotechnology, 2007)
The gene cluster catRABC, involved in catechol degradation, was isolated from Rhodococcus erythropolis CCM2595. The genes catA, catB, catC, and the divergently transcribed catR code for catechol 1,2-dioxygenase, cis,cis-muconate cycloisomerase, muconolactone isomerase, and an IclR-type transcriptional regulator, respectively. Measurements of catechol 1,2-dioxygenase activity showed that the expression of catA is induced by phenol but not by catechol or cis,cis-muconate. The activity of catechol 1,2-dioxygenase was repressed by succinate, but no repression by glucose was observed. The transcription start points of catA and catR were determined by primer extension analysis, and the respective promoters (P-catA and P-catR) were thus localized. Measurements of promoter activity during batch cultivation using transcriptional fusion with the gfpuv reporter gene showed that expression of the catR-catABC operon is regulated at the level of transcription. Both P-catR and P-catA are repressed by CatR, and the induction of P-catA by phenol is maintained in the absence of the repressor (in R. erythropolis DeltacatR). Two different potential binding sites for the IclR-type regulator and a recognition site for the cyclic AMP receptor protein (CRP) were identified within the intergenic region between catR and catA.
Keywords: genetická transkripce; sekvenční seřazení; kyselina jantarová; katechol-1,2-dioxygenasa; katecholy; DNA-Binding Proteins; isomerasy dvojných vazeb mezi uhlíky; sekvence nukleotidů; Promoter Regions, Genetic; DNA vazebné proteiny; Carbon-Carbon Double Bond Isomerases; DNA, Intergenic; Genes, Bacterial; Molecular Sequence Data; Transcription Factors; Transcription, Genetic; molekulární sekvence - údaje; fenol; Succinic Acid; Phenol; represorové proteiny; Rhodococcus; bakteriální proteiny; Operon; intramolekulární lyasy; Catechols; Catechol 1,2-Dioxygenase; Repressor Proteins; Base Sequence; bakteriální geny; Cyclic AMP Receptor Protein; Intramolecular Lyases; Bacterial Proteins; transkripční faktory; operon; receptorový protein pro cyklický AMP; promotorové oblasti (genetika); intergenová DNA; multigenová rodina; Multigene Family; Sequence Alignment